Pengembangan Asesmen Technological Pedagogical Content Knowledge (TPaCK) untuk Meningkatkan Kemampuan Pedagogical Mahasiswa Calon Guru Fisika - Syarif Lukman Hakim Assegaf; Eti Sukadi; Nurhayati Nurhayati (Kappa Journal, 2026)
This study aims to develop a Technological Pedagogical Content Knowledge (TPaCK)-based assessment instrument to measure and support the improvement of pedagogical competence among pre-service physics teachers. The instrument was developed in the form of reasoned multiple-choice items that integrate Content Knowledge (CK), Pedagogical Knowledge (PK), Technological Knowledge (TK), and their interrelationships within the TPACK framework in the General Physics I course, which covers fundamental mechanics concepts. The study employed a Research and Development approach using the ADDIE model, limited to the development stage. The distribution of test items indicates proportional representation of CK, PK, TK, and integrated TPaCK aspects. The developed instrument consisted of 23 items and was piloted with first-semester students of the Physics Education Study Program who had completed the General Physics I course. Item analysis included tests of validity, reliability, difficulty level, and discrimination index. The results showed that 12 items met the eligibility criteria and were considered valid and reliable as a TPaCK-based assessment instrument. These findings suggest that the developed TPaCK assessment has the potential to serve as a contextual and relevant evaluation tool for measuring the pedagogical competence of pre-service physics teachers in technology-enhanced learning environments